Otherness in various Ilonggo gay stories - Gajete, Ian (2008.)
As society continues its prejudice toward sexuality, favoring heterosexuality and disapproving homosexuality, it is not surprising that male homosexuals live a troubled life. As society displays the value of superiority of heterosexuality over homosexuality, it is not difficult to understand why male homosexuals as they subsist in a society that is so critical about sexuality thus becoming biased about it, find great difficulty obtaining feeling of belongingness and compassion in society. As socially homophobic attitudes trickle down, gays are left feeling different and excluded. These experiences are very evident in the stories orally told by gay men in Iloilo. As these stories depict gays as subjects for ostracism and discrimination, they will be subjected to the discourses in post-colonial theory as post-colonial theory has a lot to say about these experiences of male homosexuals., Otherness in post-colonial theory is a buzzword as it deals with the experiences of an inferiority subject termed as other subject. Using otherness as a framework in examining these gay stories, it is one major finding that there really is a signifying system that prioritizes straight over homosexuals. Gay people are oppressed, are facing prejudice, hostility and violence of straight biased society. It is also an important finding that the oppression starts in the family as the very form of the family works against homosexuality. One very important thing about this study is the finding that gays defy the different stereotypes held by people about them. In most cases, they are considered the inferiors but in one of the stories, a gay character proves that he can be superior over the straight man.
Thesis (Undergraduate, Bachelor of Arts in Literature) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Homosexuals; Ilonggo gays